Regional Differences in Antifungal Susceptibility of the Prevalent Dermatophyte Trichophyton rubrum - Jiang, Y. (Mycopathologia, 2020)
In vitro susceptibility testing for Trichophyton rubrum has shown resistance to terbinafine, azoles and amorolfine, locally, but epidemiological cutoffs are not available. In order to assess the appropriateness of current first-line antifungal treatment for T. rubrum in China, we characterized antifungal susceptibility patterns of Chinese T. rubrum strains to nine antifungals and also described the upper limits of wild-type (WT) minimal inhibitory concentrations (MIC) (UL-WT) based on our study and another six studies published during the last decades. Sixty-two clinical isolates originating from seven provinces in China were identified as T. rubrum sensu stricto; all Chinese strains showed low MICs to eight out of nine antifungal drugs. Terbinafine (TBF) showed the lowest MICs of all antifungal classes tested in both the Chinese and global groups, with a 97.5% UL-WT MIC-value of 0.03 mg/L. No non-WT isolates were observed for TBF in China, but were reported in 18.5% of the global group. Our study indicated that TBF was still the most active drug for Chinese T. rubrum isolates, and all strains were within the WT-population. TBF therefore remains recommended for primary therapy to dermatophytosis caused by T. rubrum in China now, but regular surveillance of dermatophytes and antifungal susceptibility is recommended. SUPPLEMENTARY INFORMATION: The online version of this article (10.1007/s11046-020-00515-z) contains supplementary material, which is available to authorized users.